Recruitment patterns, low cannibalism and reduced interspecific predation contribute to high invasion success of two Pacific crabs in northwestern Europe. (5th January 2018) - Geburzi, Jonas C.; Brandis, Dirk; Buschbaum, Christian
Abstract: Life-history traits and interactions with native species play an important role for the successful establishment of non-native species in new habitats. We investigated the recent successful invasion of the Pacific crabs Hemigrapsus takanoi and H. sanguineus to the southeastern North Sea coast with respect to their recruitment patterns, as well as interactions of juvenile with sub-adult individuals among the Pacific crabs and with native shore crabs Carcinus maenas . A field survey of juvenile native and introduced crab abundances (carapace width 1.4–10 mm) was conducted in the northern Wadden Sea, spanning 24 months from 2014 to 2016. The survey revealed different seasonal recruitment patterns of native C. maenas and both introduced Hemigrapsus species. Native shore crabs showed a single recruitment peak from June to July, while Hemigrapsus spp. mainly recruited from August to early September, but recruits occurred in low densities throughout the winter until the end of the following spring season. Field experiments on the effects of larger crabs on the recruitment intensity showed that recruitment of H. takanoi was enhanced by the presence of larger congeners, but remained unaffected by larger C. maenas . Recruitment of juvenile C. maenas, by contrast, was reduced by the presence of larger Hemigrapsus spp. Additional laboratory experiments revealed high rates of cannibalism on newly recruited C. maenas by subadult conspecifics as well as strong predation by larger Hemigrapsus spp. In contrast, newly recruited Hemigrapsus spp. had a much lower risk of being preyed on by subadult conspecifics and native shore crabs. Our results suggest that the timing of recruitment in combination with low intraspecific competition and reduced predation pressure by native shore crabs are crucial for the rapid and ongoing establishment of Hemigrapsus spp. in the Wadden Sea. Graphical abstract: Highlights: Asian crabs Hemigrapsus spp. established besides native Carcinus maenas in the southeastern North Sea. Recruitment peaks of Carcinus maenas and Hemigrapsus spp. are temporally shifted. Recruitment of C. maenas is reduced by adult Hemigrapsus spp. in field experiment. Presence of adult Hemigrapsus spp. enhances recruitment of juveniles. Timing and interaction patterns contribute to invasion success of Hemigrapsus spp.